Clinical Characteristics of Patients with Tick-Borne Encephalitis (TBE): A European Multicentre Study from 2010 to 2017 - Kohlmaier, Benno; Schweintzger, Nina A; Sagmeister, Manfred G; Švendová, Vendula; Kohlfürst, Daniela S; Sonnleitner, Astrid; Leitner, Manuel; Berghold, Andrea; Schmiedberger, Erich; Fazekas, Franz; Pichler, Alexander; Rejc-Marko, Jana; et al. (Microorganisms, 2021)
Tick-borne encephalitis (TBE) virus is a major cause of central nervous system infections in endemic countries. Here, we present clinical and laboratory characteristics of a large international cohort of patients with confirmed TBE using a uniform clinical protocol. Patients were recruited in eight centers from six European countries between 2010 and 2017. A detailed description of clinical signs and symptoms was recorded. The obtained information enabled a reliable classification in 553 of 555 patients: 207 (37.3%) had meningitis, 273 (49.2%) meningoencephalitis, 15 (2.7%) meningomyelitis, and 58 (10.5%) meningoencephalomyelitis; 41 (7.4%) patients had a peripheral paresis of extremities, 13 (2.3%) a central paresis of extremities, and 25 (4.5%) had single or multiple cranial nerve palsies. Five (0.9%) patients died during acute illness. Outcome at discharge was recorded in 298 patients. Of 176 (59.1%) patients with incomplete recovery, 80 (27%) displayed persisting symptoms or signs without recovery expectation. This study provides further evidence that TBE is a severe disease with a large proportion of patients with incomplete recovery. We suggest monitoring TBE in endemic European countries using a uniform protocol to record the full clinical spectrum of the disease.
Keywords: meningomyelitis; vaccine-preventable disease; peripheral paresis; tick-borne encephalitis; central paresis